Meningkatkan Hasil Belajar Siswa Dalam Materi Operasi Hitung Bilangan Bulat Pada Mata Pelajaran Matematika Dengan Menggunakan Model Pembelajaran Time Games Tournament (TGT) Pada Kelas V SD - Siti Patimah; Rifki Arif Nugraha; Yeni Sulaeman; Ade Farid Hasyim (Desanta Publisher, 2023)
This study aims to improve student learning outcomes in mathematics subject matter for class VSDN Panjangjaya 2 Academic Year 2023/2024 by applying the Time Games Tournament (TGT)learning model, learning model and to be able to improve student learning outcomes in materialarithmetic operations on integers in mathematics class V SDN Panjangjaya 2, MandalawangiDistrict, Pandeglang Regency, Banten Province.The method used in this research is Classroom Action Research (PTK) which is collaborative.Researchers collaborate with teachers in planning, identifying, observing, and carrying out theactions that have been designed. The research design used was a spiral system Classroom ActionResearch with the Hopkins and John Elliot models which began with preliminary actions thencontinued with planning, action, observation, and reflection. The research was conducted in 2 cycles.The research was carried out at SDN Panjangjaya 2, Panjangjaya Village, Mandalawangi District,Pandeglang Regency. The samples selected in this study were fifth grade students, totaling 20students consisting of 8 male students and 12 female students. In this research there are severalstages that will be carried out from the results of pre-cycle research, cycle I, and cycle II.The results of the study revealed that in the pre-cycle conditions, 4 students completed their studiesor about 20% of the 20 students, with an average class score of 46.05. After the first cycle activitieswere carried out, the number of students who completed their studies became 12 out of 20 studentsor around 60% with an average score of 68.55. In cycle II, it is known that there are 17 students outof 20 students who have successfully completed their studies, with an average score of 78.6 with acompleteness percentage of 85% and can be said to be successful.The increase in student learning outcomes in mathematics subject matter of integer arithmeticoperations is motivated by the use of an effective and fun learning model so that it can motivatestudents' interest in learning to be better. The learning model used is the Cooperative Team GamesTournament (TGT) learning model.